Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

substitution of y= 4x-3 3x-2y=16

Sagot :

Answer:

(-2,-11)

Step-by-step explanation:

3x-2(4x-3)=16

3x-8x+6=16

-5x=10

x=-2

Plug back in

y=4(-2)-3

y=-8-3

y=-11

Answer:

(-2,-11)

Step-by-step explanation:

y= 4x-3

3x-2y=16 <— substitute y from above

——————————————————————————-

3x-2y = 16

3x-2(4x-3) = 16

3x-8x+6 = 16

-5x + 6 = 16

-5x ÷ 10

x = -2

——————————————————-

Substitute the x from above to any equation to get the y value

3x-2y=16

3(-2)-2y=16

-6 - 2y = 16

-2y = 22

y = -11

——————————————————-———————

(-2,-11)